The Association between Genetic and Racial Factors in Ethanol Containing Beverages Metabolism and Health Risks in Human - Yen, Hoang Thi Thu (VNU Journal of Science: Natural Sciences and Technology; Vol 39 No 2DO - 10.25073/2588-1140/vnunst.5094, 2023)
Ethanol containing beverages (alcoholic beverages) are socially acceptable beverages that are expected to provide refreshment, satisfaction and stress relief. Common types of ethanol containing beverages include: wine, beer, and syrup. According to the World Health Organization, alcohol abuse is a risk factor for high mortality and many diseases in humans such as fatty liver, hepatomegaly, cirrhosis, liver cancer, larynx cancer, nasopharynx cancer, stomach and esophageal cancer,… In human, ethanol is eliminated mainly through metabolism in two ways: Oxidative pathway with the participation of enzymes: alcohol dehydrogenase (ADH), aldehyde dehydrogenase (ALDH), cytochrome P450 and catalase; non-oxidative pathways involving phospholipase and fatty acid ethyl ester (FAEE) synthase. Alcohol abuse is believed to be caused by genetic factors ( ADH , ALDH ,...), psychological and social factors. Single nucleotide polymorphisms (SNPs) in genes encoding enzymes involved in ethanol metabolism helped explaining why certain ethnic groups and individuals have higher or lower ethanol-related health risks and development of alcohol abuse syndrome. In Vietnam, using ethanol containing beverages  is a habit imbued with traditional culture. At the same time, wine and beer abuse is already a problem and causes many serious consequences for public health, family happiness and social safety. Meanwhile, the concept that drinking alcohol helps relieve nervous tension is common, many people still feel subjectively drinking alcohol to be healthier. Some studies have shown differences about SNPs of gene encoding enzymes involved in ethanol metabolism in Vietnamese. Therefore, it is necessary to study the relationship between SNPs of these genes with alcohol and beer drinking habits leading to abuse and the risks of ethanol-related diseases.